"Suplementacion proteica para el mantenimiento y fortalecimiento a las colmenas de abejas (Apis mellifera) Recinto Aguas Frias-Mocache 2018". - Avilés Rendon, Yojaira Elizabeth (2019)
The present study was carried out in the cold water precinct of the Mocache Canton, with the objective of evaluating the effect of protein supplementation (16-19-22-25%) on Bee colonies (Apis mellifera.), Where 16 beehives were evaluated. bees, the variables to study were; population status, food consumption, incidences of diseases and cost of treatments, where a completely random design was used with four treatments and four repetitions (each experimental unit was constituted by a hive), all the treatments were supplied in the form of cake where the ingredients were: dry and ground pollen, sugar, soybean and honey flour (T1), pollen, sugar, soy and honey flour (T2), brewer's yeast, sugar, soybean meal and honey (T3) , pollen, sugar, soybean meal and honey (T4). The supplementation was delivered every seven days for seven weeks, in the rainy season of December 2018 to February 2019. The results were evaluated in the Infostat statistical program, using the Tukey variance analysis with a level of significance of 5%. obtaining as a result that there was no statistically significant difference between the variable population status, and food consumption, for the variable incidence of diseases it was observed that the hives were free of more common diseases such as: American and European foulbrood, for the acarus varroa destructor took samples which showed that the average percentage of infestation was less than 5% in each hive, for which it indicates that it is not necessary to apply any acaricide treatment since it is tolerated by the same bees, in addition an economic analysis of the cost of treatments where the treatment based on 19% of protein was the lowest cost, which shows us that there is no significant statistical difference between treatments can apply the lowest cost supplement in times of food shortages. Key words: Soybean meal, hives, brewer's yeast, Apis mellifera, pollen, honey.